"Ethanol–water exchange" nanobubbles templated hierarchical hollow β-Mo2C/N-doped carbon composite nanospheres as an efficient hydrogen evolution electrocatalyst. Issue 14 (21st March 2018) - Diao, Lechen; Qin, Jian; Zhao, Naiqin; Shi, Chunsheng; Liu, Enzuo; He, Fang; Ma, Liying; Li, Jiajun; He, Chunnian
Abstract : "Ethanol–water exchange" nanobubbles were utilized to produce hollow β-Mo2 C/N-doped carbon nanospheres for use as an efficient hydrogen evolution electrocatalyst. Abstract : Hollow β-Mo2 C/N-doped carbon composite nanospheres constructed by mesoporous ultrathin carbon nanosheets anchored with ultrasmall β-Mo2 C nanoparticles were synthesized through a facile green process. Nanobubbles generated by ethanol–water exchange were utilized as templates for the core, while the precipitates in the solution were directly adopted as the emulsion stabilizer and the shell. Upon the self-polymerization of dopamine, a robust shell consisting of the Mo–polydopamine complex was formed. The size of the as-obtained hollow Mo–polydopamine nanospheres can be tuned by varying the type of gas, which is proportional to the supersaturation of gas. These precursors of hollow Mo–polydopamine nanospheres were then converted into hollow β-Mo2 C/N-doped carbon composite nanospheres by high-temperature carbonization treatment. The N-doped carbon matrix can act as an electron conductor and facilitate the prevention of the migration and aggregation of the Mo2 C nanoparticles, while the ultrafine Mo2 C nanoparticles can achieve maximum material utilization for hydrogen evolution electrocatalysis. In addition, the mesoporous 2D nanosheets combined with their constructed 3D hollow structures can expose numerous active catalytic sites while enabling free diffusion of the electrolyte and mass transfer. As a result, the hollow β-Mo2 C/N-doped carbon composite nanospheres exhibit low overpotentials and robust cycling stability in both acidic and alkaline electrolytes.